(untitled) (Revista de Estudios Brasileños, 2023)
This research work, in an essay format, seeks to demonstrate and to understand, in general, a commercial relationship between spaces that supply raw materials in natura, in the Brazilian Amazon, with countries in Southeast Asia, especially China. This trade forms a production chain related to the fishing of fish species with high commercial value for their meat and meat products. These products derived from some species of fish are exported through ports and warehouses, mainly from the state of Pará (Belém, Bragança and Vigia) to Asian and European countries. We are highlighting here in this work the “Grude” of the fish (popularly called) which is the swimming bladder extracted, mainly from species of catfish and hake, such as gurijuba (Hexanematichthys parkeri) and yellow hake (Cynoscionacoupa). The focus of this study is on the municipality of Vigia, where it stands out as a fishing warehouse and participates in this market highlighted in this research. The result of this description and characterization presented here is to reveal a marked process of the dependence and fragility of Brazilian regional production in relation to the Chinese market, contradicting all the goals of integration and equity of the BRICS component countries.